Role of EDTA and cysteine hydrocloride as additivies in EYC and TEFC . extenders for preservations of beetal bulk’s spermatozoa - SINGH, K H MANI; SINGH, M P; SINHA, A K; SINGH, D K (The Indian Journal of Animal Reproduction, 2023)
The semen sample ofBeetal bucks extended in six extenders ( EYC, EYC + EDTA, EYC + Cysteine Hcl, TEYFC. TEYFC + EDTA and TEYFC + Cysteine Hcl) and preserved at refrigerator temperature were evaluated for motility, livability and abnonnality up to 96 hours at 24 hours interval.The effects of extender and additive on seminal attributes were significant ( P 0.0 I). The post preservation seminal attributes were better in TEYFC extender incorporated with Cysteine Hcl as compared to other extenders , indicating that TEYFC is an ideal semen diluent as compared to EYC and that inclusion ofO.0 I% Cysteine Hcl in both extenders showed beneficial effect towards improving the keeping quality of liquid semen of Beetal bucks.